Threshold height (h′F)c for the meridional wind to play a deterministic role in the bottom side equatorial spread F and its dependence on solar activity - Jyoti, N.; Devasia, C.V.; Sridharan, R.; Tiwari, D. (My University, 2004)
[1] Detailed investigations have been carried out on the occurrence of bottom side Equatorial Spread F (ESF) and the thermospheric meridional wind characteristics just before the former's initiation using ground based ionospheric data corresponding to the equinoctial periods of 1993–1998, from Trivandrum (8.5°N, 76.5°E, dip = 0.5°N) and Sriharikota (13.7°N, 80.2°E, dip ∼ 10°N) in the Indian longitudes. Critical analysis of the base height of the F-region h′F at the time of triggering of ESF and the polarity of the meridional winds revealed that, if the h′F is above a certain level ESF occurred under both equatorward and poleward wind conditions. Below that level, ESF occurred only when equatorward winds were present implying that the equatorward winds must somehow be able to offset the reduced growth rate of the plasma instability responsible for ESF. A plausible explanation linking Equatorial Ionization Anomaly (EIA) and the consequent Equatorial Temperature and Wind Anomaly (ETWA) and the consequent neutral dynamics effectively enabling the instability even at lower height has been offered. The threshold height (h′F)c gleaned out on the basis of the polarity of the meridional winds has been shown to bear a linear relation to the solar activity and sheds light on the enigmatic short and long term variability of ESF.
Keywords: Equatorial spread F; Solar activity; F-region; Ionospheric dynamics